Analisis Kualitas Pelayanan dan Fasilitas untuk Meningkatkan Kepuasan Pelanggan pada Bisnis Hotel - Boka, Ryalest M. B.; Turang, Frangky Yongki; Boka, Ronald Yusak; Poli, Altje Ester (Universitas Sam Ratulangi, 2026)
The urgency of this research is to improve the quality of service of hotel business actors to increase customer satisfaction and the quality of the tourism industry in Tomohon City. This research was conducted to help hotel business actors to improve customer satisfaction by analyzing the quality of service and facilities as the main variables with a marketing management model, because good quality of service and facilities are the main factors to strengthen the hotel business. The purpose of this research is to determine and analyze the quality of service and facilities using a marketing management model to improve customer satisfaction to be able to solve problems related to the National Research Master Plan on the focus of Social Humanities with the theme of Tourism and the Creative Economy and the topic of Creative Tourism Development as well as solving problems related to the second goal of the creative economy sector.